The relationship of belief and quality of life of HIV-infected housewives - Diah Priyantini; Daviq Ayatulloh; Yuanita Wulandari (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Housewives with human immunodeficiency virus (HIV) infection may experience decreased quality of life, especially due to transmission of infection through their partners. In order to improve their health management and increase quality of life, confidence is needed. The purpose of this study was to analyze the relationship of belief and quality of life of HIV-infected housewives.